Subtropical and flower crops breeding at the Subtropical Scientific Centre - A. V. Ryndin; R. V. Kulyan; N. A. Slepchenko (Вавиловский журнал генетики и селекции)
This paper presents the results on the breeding work carried out by the Subtropical Scientific Centre of the Russian Academy of Sciences. Currently, the Centre’s breeders are doing a lot of work aimed at breeding new fine yielding cultivars of subtropical and flower crops that will be resistant to growing conditions; they include kaki persimmon, feijoa, mandarin, freesia, crown anemone, pelargonium and chrysanthemum. The sources of high-level priority traits in flower crops that are valuable for further breeding in order to improve decorative (colour, flower shape, inflorescence), economic and biological traits (flowering period, a large number of flowers in the inflorescence, storage period of cut flowers, disease resistance, high reproduction coefficient) were recorded. The aim of the research is to improve the subtropical and flower crops assortment. The objects of the research were 989 hybrid forms: 136 citrus crops, 56 persimmon, 36 feijoa, 38 tea plant, 11 pear, 24 hazel, 108 freesia, 398 crown anemone, 120 pelargonium and 62 chrysanthemum hybrids. New cultivars with a complex of valuable traits have been created as a result of the scientific work. Over the past five years, FRC SSC of RAS has created 50 new cultivars: 26 pelargonium, 15 anemone, 5 freesia, 2 chrysanthemum, 1 persimmon and 1 apple and submitted them to the State Cultivar Commission. The “State Register of Selection Achievements Authorized for Use for Production Purposes” has included 63 cultivars developed by FRC SSC RAS, including 26 pelargonium, 13 anemone, 9 chrysanthemum, 7 freesia, 4 hazel, 3 feijoa and 1 tea plant cultivars. 46 patents for breeding achievements have been obtained.